The mutual influence between the artistic space of the painting and the cinematic image - Assist. Lectu. Ieman Faris Salman (Journal of College of Education, 2025)
The relationship between the visual arts and cinema manifests through the interplay that occurs between them on both aesthetic and technical levels, and then through the exchange of roles between them throughout history. The visual dimension occupies an important space within the framework of the cinematic image and contributes to aesthetic impact in multiple ways. The same can be said if we take a reverse reading, especially since the presence of the cinematic component in the visual arts has begun to increasingly emerge in the age of the image we are living in, with all its diverse forms due to the colossal technological development in this century. The aesthetic dimension of the cinematic image can be addressed through cinematic theories and trends as they open up to literary, sociological, philosophical criticism, and art history. This cognitive and aesthetic relationship is affirmed and manifested through other visual expressive forms such as video art, photography, advertising, and visual arts. Visual art is the art that expresses form in its stillness or motion, while plastic cinema is also a constantly transforming, renewing composition that is uninterrupted and perpetually forming, ephemeral, emerging, renewed through a movement created by illusion, yet it gives it great reality that sketches the truth and interaction between the viewer and the screen, that is, a moving visual drama.